Deixis Used in Top Five Waldjinah’s Popular Keroncong Song Lyrics - Gede Arga Anggara (Master Program in Linguistics, Diponegoro University, 2016)
This study aims to describe the types of deixis used in top five Waldjinah’s popular keroncong song lyrics, to find out the dominant types and the reason why the type of deixis was dominantly used. The song lyrics are associated in the study of deixis since they express the singer’s or song writer’s feeling or emotion represented by some expressions of human thoughts, ideas, opinions. The descriptive method with qualitative approach was involved in this study. The data were obtained from top five popular keroncong songs lyrics performed by Waldjinah entitled Walang Kekek, Yen Ing Tawang Ana Lintang, Anoman Obong, Tanjung Perak and Rondo Kempling. Based on the findings, the person deixis was found as the most dominant type. It is in accordance with the function of person deixis that mostly deals with people interaction. The person deixis found in this study is used to maintain interaction between Waldjinah as a singer and her audience. The importance of using person deixis especially in keroncong song lyrics should be included by the song writers in order that young generations as the listeners who will preserve the keroncong song existence, become more understand even enjoy listening to.